Mineralogical and Geochemical analysis of the sediments surrounding the Main Drain Area, Middle of Iraq - Al-Mallah, Inass; Al-Suhail, Qusay; Albadran, Adel (Iraqi Journal of Science, 2022)
Fifty five surface and subsurface soil samples were taken from the area between Tigris and Euphrates Rivers along the Main Drain course from north Baghdad to Basrah to evaluate the geochemical, physical characteristics and the probability contamination of these samples. The study area is covered by Quaternary sediments of complex alternation of sand, silt and clay. Significant variation in the textural content of the present soils is observed, where the northern and southern parts are characterized by silt predominance, while sand is prevailing in the central parts as a result of the extensive spreading of aeolian deposits represented mostly by sand dunes. Mineralogical analysis explains wide variations in the heavy minerals distribution of different origins and that all of these minerals reflect the same distribution patterns. Calcite and quartz are the minerals of non-clay fraction, whereas montmorellonite, kaolinite, and chlorite are the key clay mineral in the present soils. No geochemical anomalous concentration of the trace elements in the soils can be detected except of few locations revealing potential pollutions. Clustering technique of the surface and subsurface soils shows presence of five and six groups respectively. This confirms the complexity and diversity nature of the sedimentary environment. Discriminante analysis of the surface soils indicates that salinity and sand content are the main discriminating variables responsible for grouping the soils, whereas sand, salinity and the main oxides are the discriminating variables for grouping subsurface soils. These statistical analysis and other relations results confirm that no clear indication concerning trace element pollution can be detected in the study area soils.